Hip flexor and knee extensor muscularity are associated with sprint performance in sprint-trained preadolescent boys - Tottori, N.; Suga, T.; Miyake, Y.; Tsuchikane, R.; Otsuka, M.; Nagano, A.; Fujita, S.; Isaka, T. (Pediatric Exercise Science, 2018)
Purpose: We attempted to determine the relationships between the cross-sectional area (CSA) of the trunk and lower limb muscles and sprint performance in male preadolescent sprinters. Methods: Fifteen sprint-trained preadolescent boys (age 11.6±0.4 y) participated in this study. The CSAs of the participants` trunk and lower limb muscles were measured using magnetic resonance imaging, and these muscles were normalized with free-fat mass. To assess participants` sprint performance, sprint time and variables during the 50-m sprint test were measured. The sprint variables were expressed as their indices by normalizing with body height. Results: The relative CSAs of psoas major, adductors, and quadriceps femoris were significantly correlated with sprint time (r=-.802, -.643, and -.639). Moreover, the relative CSAs of these muscles were significantly correlated with indices of sprint velocity (r=.694, .612, and .630) and step frequency (r=.687, .740, and .590) but not with that of step length. Conclusions: These findings suggest that greater hip flexor and knee extensor muscularity in male preadolescent sprinters may help achieve superior sprint performance by potentially enhancing their moments, which may be induced by increased step frequency rather than step length during sprinting.